Improvement of Interstellar Material and Energy Flows - Stenis, Jan (Archives of Business Research, 2021)
Objectives A novel approach is suggested to utilize the inherent forces of the universe for the benefit of mankind, by applying the model for Efficient Use of Resources for Optimal Production Economy (EUROPE) to improve the major flows of gas, dust, material and energy between stars and galaxies. This endeavour is regarded as promoting the altruism and benevolence by increasing life-forms’ chances to survive. Methods It is shown how the torus-shaped flows of gas, dust material and energy between stellar bodies in cosmos can be improved with the EUROPE model in order to preserve universe and secure its existence by allocating shadow costs to waste-like flows and unwanted radiation in this torus. The fewer shadow costs being allocated to the stellar residuals, the more efficient the cosmic torus flows, expressed in equivalents of antimatter released, by inducing incentives to improve the conditions for all inhabitants. Results The methodology promotes the economy when travelling in space, advances the technology used and improves the environment, when outer space in the future is explored and exploited. A single key factor enables monitoring, managing and evaluating the development of universe and the flows of gas, dust, material and energy between various stellar objects, such as the distant stars and whole galaxies. Conclusions I recommend using the EUROPE model to monitor, manage and evaluate the wastes and spillages of all material and energy phenomena throughout the known universe, to uphold its very existence.